The Role of Social Media in Increasing Brand Awareness in E-Commerce Businesses - Rusdun Kamil Ramadhan; Wildan Setiawan; Wildhan Romdhoni; Miftahur Rohmah; Afaful Ummah (Regulate: Jurnal Ilmu Pendidikan, Hukum dan Bisnis, 2025)
This study aims to describe the role of social media in increasing brand awareness in e-commerce businesses in Indonesia. Using a descriptive qualitative approach through a literature review method, this study analyzed various scientific publications from 2019-2024. The results of the study indicate that social media plays a significant role in increasing brand awareness by up to 67% through two-way interactions, the spread of viral content, and broad audience reach. Platforms such as Instagram, TikTok, and Facebook are the primary choices, with visual content generating 94% higher engagement than text content. Key strategies identified include creative content marketing, influencer marketing with a focus on micro-influencers, social media advertising with precise targeting, and data analytics-based effectiveness measurement. Micro-influencers have been shown to have a 60% higher engagement rate than mega-influencers due to their authenticity and closeness to the audience. Short videos (15-60 seconds) can increase brand awareness by up to 80%, while retargeting ads have a 70% higher conversion rate. Challenges faced include changes in platform algorithms, intense content competition, fake followers, and building trust in the digital era. This research provides theoretical contributions to the study of digital marketing communications and practical benefits for e-commerce players in designing effective and adaptive social media strategies to the dynamics of digital consumer behavior.